Simulation Innovation: A Novel Simulation Guide for Building Community Simulation Capacity in Pandemic Preparedness. Issue 6 (December 2020) - Drake, Hilary; Abbey, Darin; Holmes, Chelsea; Macdonald, Anna; Mackinnon, Laura; Slinn, JoAnne; Baylis, Jared
Abstract : Summary Statement: The coronavirus disease 19 (COVID-19) pandemic, caused by severe acute respiratory distress syndrome coronavirus 2, has spread globally and requires effective preparedness within healthcare institutions. The British Columbia Simulation Network COVID-19 Simulation Guide was created to disseminate information throughout the province of British Columbia, Canada, and to allow simulation educators, from novice to expert, to participate in COVID-19 simulations. As of July 15, 2020, the guide had been downloaded 465 times from the British Columbia Simulation Network website, with downloads in 41 countries around the world. The guide has been frequently updated and revised to reflect evolving guidelines as new knowledge about COVID-19 was established. Abstract : Supplemental digital content is available in the text.